The effects of school environment on learning outcomes - Ralia Happy Aprilla; Agil Al Idrus; Baiq Sri Handayani; Gito Hadiprayitno (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The school environment is one of the learning resources that can obtain quality learning processes and outcomes for students. This study purpose: 1. analyze the effects of school environment advantages as a learning resource on affective learning outcomes; 2. analyze the effects of school environment advantages as a learning resource on psychomotor learning outcomes; 3. analyze the effects of school environment advantages as a learning resource on cognitive learning outcomes. This type of research is a quasi-experiment with a nonequivalent control group design. The determination of the research sample was carried out using the purposive sampling technique. The data were collected by testing the affective, psychomotor, and cognitive learning outcomes and analyzed by analyzing covariances. The study results indicate that the advantages of the school environment as a learning resource have an influence on learning outcomes in the affective, psychomotor, and cognitive aspects (p < 0.05).